Bidding behaviour in the ECB's main refinancing operations during the financial crisis - Jens Eisenschmidt; Astrid Hirsch; Tobias Linzert (European Central Bank (ECB), 2009)
Liquidity provision through its repo auctions has been one of the main instruments of the European Central Bank (ECB) to address the recent tensions in financial markets since summer 2007. In this paper, we analyse banks' bidding behaviour in the ECB's main refinancing operations (MROs) during the ongoing turmoil in money and financial markets. We employ a unique data set comprising repo auctions from March 2004 to October 2008 with bidding data from 877 counterparties. We find that increased bid rates during the turmoil can be explained by, inter alia, the increased individual refinancing motive, the increased attractiveness of the ECB's tender operations due to its collateral framework and banks' bidding more aggressively, i.e. at higher rates to avoid being rationed at the marginal rate in times of increased liquidity uncertainty.
Keywords: E52; D44; C33; C34; 330; Bidding Behavior; Central Bank Auctions; Financial Market Turmoil; monetary policy instruments; Panel Sample Selection Model; Geldmarkt; Offenmarktpolitik; Auktion; Refinanzierung; Bankenliquidität; Finanzkrise; EU-Staaten